ANALISIS KOMUNIKASI KERJA DALAM MENINGKATKAN KINERJA PEGAWAI PADA KELURAHAN DEPOK KECAMATAN PANCORAN MAS KOTA DEPOK - Sere Novianti Manalu; Yulies Herni (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the causal factors, forms, and strategies for handling work communication on employee performance in Depok Village, Pancoran Mas District, Depok City. The study used a descriptive qualitative method with data collection techniques through observation, in-depth interviews (FGD), and documentation. The research subjects consisted of 9 informants and one key informant. The results of the study indicate that employee work communication in the village has been running well, but there are still problems found triggered by ineffective communication, miscommunication between employees, differences of opinion between employees, lack of understanding of leadership instructions, and limited feedback in communication. Ineffective forms of work communication can cause miscommunication that is not optimally felt by employees so that it can affect employee performance and the quality of public services. However, most employees are able to deal with communication by carrying out the process of conveying and exchanging information, ideas, or instructions between members of the organization which is carried out formally or informally, with the aim of creating a common understanding and supporting the completion of joint tasks. Leadership support and a fairly positive work atmosphere help employees maintain their performance. These findings emphasize the importance of regular work communication evaluations, improving collaboration between employees, accelerating the flow of information, minimizing work errors, building harmonious work relationships, supporting responsive public services and open communication to create a healthy work environment so that employee performance remains optimal.